HGG-07. THE DIVERSITY OF MOLECULAR CHARACTERISTICS IN PEDIATRIC HIGH-GRADE GLIOMAS. Issue 2 (22nd June 2018) - Kondo, Akihide; Fujimura, Junya; Akiyama, Osamu; Suzuki, Mario; Tamaichi, Hiroyuki; Arai, Hajime
Abstract: High-grade gliomas are challenging tumor to treat in both adult and pediatric patients. Although the incidence of high-grade glioma in the pediatric population is less than that in the adult population, the prognosis of this tumor seems to be better in pediatric patients than in adult patients. Especially in neonatal patients, even a case of spontaneous resolution of tumor was reported, while the patients over 10 years old are difficult to control the progression of tumors. Then, we examine molecular characteristics of high-grade gliomas in 6 pediatric patients according to patients' ages, those are from 24 days old to 13 years old. Our analysis showed the status of molecular was inconsistent by ages. Based on these observations, we think that high-grade gliomas in pediatric patients may have a diversity of molecular characteristics depending on the age of onset of tumors.